Photocatalytic removal of Escherichia coli from aquatic solutions using synthesized ZnO nanoparticles a kinetic study. - Alikhani, Mohammad-Yousef (Water Science and Technology)
Development of effective and low-cost disinfection technology is needed to address the problems caused by an outbreak of harmful microorganisms. In this work, an effective photocatalytic removal of Gram-negative bacteria Escherichia coli from aqueous solution was reported by using ZnO nanoparticles under UV light irradiation. The effect of various parameters such as solution pH, ZnO dosage, contact time and initial E. coli concentration were investigated. Maximum photocatalytic disinfection was observed at neutral pH because of the reduced photocatalytic activity of ZnO at low and high pH values originated from either acidic/photochemical corrosion of the catalyst and/or surface passivation with Zn(OH)2. As the ZnO dosage increased, the photocatalytic disappearance of E. coli was continuously enhanced, but was gradually decreased above 2 g/L of ZnO due to the increased blockage of the incident UV light used. The optimum ZnO dosage was determined as 1 g/L. Photocatalytic removal of E. coli decreased as initial E. coli concentration increased. Three kinetic models (zero-, first- and second-order equations) were used to correlate the experimental data and to determine the kinetic parameters.